2020
DOI: 10.1111/tid.13234
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus reactivation in kidney transplant patients with resolved hepatitis B virus infection: Risk factors and the safety and efficacy of preemptive therapy

Abstract: Background: Hepatitis B virus (HBV) reactivation is associated with complications and adverse outcomes in patients with clinically resolved HBV infection who are seronegative for hepatitis B surface antigen (HBs Ag), and seropositive for hepatitis B core antibody (HBc Ab) and/or hepatitis B surface antibody (HBs Ab) before kidney transplantation (KT). Methods:We retrospectively analyzed 52 patients with resolved HBV infection who were HBV-DNA negative. HBV-DNA after KT was evaluated, and the occurrence of HBV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 29 publications
1
13
1
Order By: Relevance
“…A group of Japanese investigators reviewed 52 patients with resolved HBV infection who underwent kidney transplantation and found that age and anti-HBc titer to be significant risk factors for HBV reactivation. 12 Our study did not evaluate anti-HBc titers, and we did not find age to be a significant risk factor for reactivation. However, we did find delayed graft function to be a significant predictor of HBV reactivation.…”
Section: Discussioncontrasting
confidence: 53%
See 4 more Smart Citations
“…A group of Japanese investigators reviewed 52 patients with resolved HBV infection who underwent kidney transplantation and found that age and anti-HBc titer to be significant risk factors for HBV reactivation. 12 Our study did not evaluate anti-HBc titers, and we did not find age to be a significant risk factor for reactivation. However, we did find delayed graft function to be a significant predictor of HBV reactivation.…”
Section: Discussioncontrasting
confidence: 53%
“…Age has been shown to be a factor associated with HBV reactivation based on a previous study; therefore, it was also included in our model. 12 Our multivariate logistic regression model demonstrated that the absence of HBV prophylaxis did not predict the development of HBV reactivation in our patient population.…”
Section: Resultsmentioning
confidence: 66%
See 3 more Smart Citations